2019
DOI: 10.1371/journal.pgen.1007827
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inheritance of telomere length in wild birds

Abstract: Telomere length (TL) predicts health and survival across taxa. Variation in TL between individuals is thought to be largely of genetic origin, but telomere inheritance is unusual, because zygotes already express a TL phenotype, the TL of the parental gametes. Offspring TL changes with paternal age in many species including humans, presumably through age-related TL changes in sperm, suggesting an epigenetic inheritance mechanism. However, present evidence is based on cross-sectional analyses, and age at reprodu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 58 publications
(79 reference statements)
5
75
0
Order By: Relevance
“…Studies in wild populations have provided mixed evidence for PAC and MAC effects. Studies from different taxa, with a variety of mating systems, have shown a negative PAC effect (Bouwhuis et al, 2018;Criscuolo, Zahn, & Bize, 2017;Olsson et al, 2011), including a longitudinal (Bauch, Boonekamp, Korsten, Mulder, & Verhulst, 2019) and an experimental manipulation (Noguera, Metcalfe, & Monaghan, 2018) study. However, other studies have reported no PAC or MAC effect on offspring telomere length (Heidinger et al, 2016;McLennan et al, 2018;Froy et al, 2017;Belmaker, Hallinger, Glynn, Winkler, & Haussmann, 2019) or a positive MAC effect (Asghar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in wild populations have provided mixed evidence for PAC and MAC effects. Studies from different taxa, with a variety of mating systems, have shown a negative PAC effect (Bouwhuis et al, 2018;Criscuolo, Zahn, & Bize, 2017;Olsson et al, 2011), including a longitudinal (Bauch, Boonekamp, Korsten, Mulder, & Verhulst, 2019) and an experimental manipulation (Noguera, Metcalfe, & Monaghan, 2018) study. However, other studies have reported no PAC or MAC effect on offspring telomere length (Heidinger et al, 2016;McLennan et al, 2018;Froy et al, 2017;Belmaker, Hallinger, Glynn, Winkler, & Haussmann, 2019) or a positive MAC effect (Asghar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies to date in non-human species indicate that this might not be a simple restoration to the average telomere length of the parents. Most importantly in the context of this review, studies of birds, reptiles, and non-human mammals have reported that older fathers have offspring with shorter telomeres [24,91,[109][110][111], though a positive correlation between male and female age within a breeding pair often makes it difficult to separate maternal and paternal effects in natural populations [112]. In controlled conditions using laboratory mice, offspring from older fathers have been reported to have shorter telomeres [91].…”
Section: (B) Telomere Attrition In the Germlinementioning
confidence: 94%
“…[ 24 ] One mechanism that may be particularly important in these contexts is telomeres. [ 23,25–28 ] Telomeres are highly conserved, repetitive, sequences of DNA at chromosome ends that enhance genome integrity, but shorten during normal cell division and in response to stress. [ 29 ] Once telomeres become critically short, cells stop dividing and both cell loss and the accumulation of senescent cells are expected to contribute to organismal aging.…”
Section: Parental Age and Offspring Telomeresmentioning
confidence: 99%
“…[35]. Telomere length is heritable, but accumulating evidence suggests that the age of the parents at the time of offspring production can also influence offspring telomeres, [ 27,36,37 ] which may have important consequences for offspring longevity.…”
Section: Parental Age and Offspring Telomeresmentioning
confidence: 99%
See 1 more Smart Citation